THE INFLUENCES OF QIRO’ATI IN LEARNING AL-QUR’AN AND RELIGIOUS ATTITUDES ON STUDENTS’ EMOTIONAL QUOTIENT - Khozanah; Susanto, Ahmad; Hadi, Muhamad Sofian (Edutainment, 2025)
This research aims to measure the influences of the Qiro'ati method and religious attitudes on the emotional intelligence of students at SD Lab School FIP UMJ. The method used is quantitative with survey approach. Data are collected through three questionnaires, each consisting of 30 statements with a 5-point Likert scale, including the Qiro'ati method, religious attitudes, and emotional intelligence. Total of 274 students in grades 4, 5, and 6 paticipated as respondents. The results of linear regression analysis shows that the Qiro'ati method has a significant effect on students' emotional intelligence with a contribution of 47%. Religious attitudes also have a significant influence on emotional intelligence with a contribution of 30%. Apart from that, the results of the F test show that simultaneously the Qiro'ati method and religious attitudes have a significant effect on students' emotional intelligence. Thus, it can be concluded that the application of the Qiro'ati method in learning the Al-Qur'an and students' religious attitudes together can increase their emotional intelligence both in the school environment and in everyday life.